The lamplighter group L(h)n - Mamaril, Mark Camilo C (Archīum Ateneo, 2016)
This paper discusses a finite group associated to a machine called a lamplighter, having n lamps with h settings arranged in a circle around a single lighter. The properties of the group are discussed. Criteria for determining whether group elements are conjugates, commutators or in the center are established.